Personal Identity and Vocational Decision Difficulties: The Teenager Greek Immigrants of the Hellenic High School of Wuppertal, Germany (World Journal of Vocational Education and Training, 2021)
The purpose of this research was to examine the relationship between the identity formation of adolescent Greek immigrants in Germany and the difficulties they encounter in making vocational decisions, as a prerequisite to the consequent selection of relevant education and training. The psychometric tools Ego Identity Process Questionnaire (EIPQ) and The Career Decision Making Difficulties Questionnaire (CDDQ), as well as an improvised demographic questionnaire, were handed out to 100 pupils of the Hellenic High School of Wuppertal. The research results were interpreted in the light of Marcia’s identity typology and Gati’s theoretical model and revealed that: (a) Adolescents with an Identity Achievement had little difficulty in choosing a career, while others had considerable difficulty. (b) There was no relevance between age groups and identity typology. (c) Genders did not differ in identity typology and vocational decision-making difficulties. Both sexes seemed to have equal difficulty in their vocational pursuits. (d) School performance did not differ according to the type of identity. (e) The higher the school grades/performance, the higher the identity inquiry. (f) The greater the difficulties of adolescents in their vocational choices, the less committed they became. (g) The high and middle educational level of mothers (but not of fathers) led to higher rates of Identity Achievement. The difficulties of adolescents’ vocational decision-making did not differ according to the educational level of their parents. (h) The duration of staying of adolescent immigrants in Germany was not correlated with difficulties in their vocational choices.